Dakwah Persuasif Nabi Musa Dalam Perspektif Komunikasi Dakwah Kontemporer - Muhammad Ridwan (INSTITUT PEMBINA ROHANI ISLAM JAKARTA, 2023)
The da’wah process carried out by the Prophet Moseswas not an easy matter. There were several obstacles to preaching, including the attitude of Pharaoh as the ruler of Egypt, who was very cruel, ruthless and authoritarian. Meanwhile, the Prophet Moses himself had a deficiency in the level of citizenship status in the country, namely as a child of Israel who was an ordinary citizen who was cared for since childhood by Pharaoh and belonged to the slave caste class. According to the author, this theme is very interesting to be studied further and then integrated with communication and da'wah science so that collaboration is established in historical aspects and contemporary da'wah communication science. In the process of carrying out his da'wah activities to King Pharaoh, Prophet Moses Used two da'wah methods, namely da’wah bi al-haal and da’wah bi al-lisan. The da’wah bi al-lisan used by the Prophet Moses included qaulan layyinan, qaulan balighan, qaulan sadidan. In carrying out the research the author uses a qualitative-descriptive method based on literature studies and synchronization of the story of the Prophet Moseswith the theory of da'wah communication. The results of this study obtained data that the da'wah used by Prophet Moses to King Pharaoh can be categorized as persuasive da'wah in the sense of using a dialogical attitude that is straight forward, serving (gentle), truthful (sadidan) without insulting, rebuking even in this case Moses was in the right position, received support from Allah and had various miracles.